The Influence of Regional Government Spending, Labor and Investment on Economic Growth in Districts/Cities in West Nusa Tenggara Province 2014-2023 - Jihan Qur’Ani Lestari; M Irwan; Siti Fatimah (Future Techno-Science, 2025)
This study aims to analyze the effect of Regional Government Spending, Labor and Investment on Economic Growth in Regencies/Cities in West Nusa Tenggara Province in 2014-2023. This research method is quantitative research with an associative approach. This study uses secondary data obtained from the Central Statistics Agency (BPS), Regional Finance Agency (BKD), Investment and One-Stop Integrated Service Agency (DPMPTSP), and Manpower and Transmigration Agency during a certain period. The analysis method used is the Ordinary Least Square (OLS) method as an estimation technique through Eviews 12 software. For the calculation using Panel Data Analysis with Model Selection Test, Classical Assumption Test and Hypothesis Test. The results of the study indicate that the Regional Government Spending variable has a positive and significant effect on economic growth. The Labor variable has a positive but not significant effect, and the Investment variable has a positive and significant effect on economic growth in West Nusa Tenggara Province. Simultaneous calculations provide results that the variables of Regional Government Expenditure, Labor, Investment have a positive and significant effect on economic growth with a large influence of 93.01% percent, and the remaining 6.99 percent is influenced by other variables not included in the model.